PERSEPSI PENGURUS KOMUNITAS FORUM UMAT ISLAM SULAWESI TENGAH TERHADAP ISI PEMBERITAAN UMAT ISLAM PADA AKUN MUSLIM CYBER ARMY MELALUI FACEBOOK - Aisia, Masyithah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
This research uses a case study method, in order to measure and find out more about a problem. In this research, several administrators in the FUI Sul-Teng community were the main sources, to find out and analyze what perceptions could be found, and what factors were the basis for the perceptions of the FUI Sul-Teng community administrators regarding the content of Muslim news. on the MCA account via Facebook. The results of this research show that there are similar perceptions regarding the content of Muslim news that appears on the MCA account, especially since the MCA account has been infiltrated by many people and social media users who have personal interests. So the information on this account is not as pure as before, which was initially formed by MCA as a means of discussion and a place to share information about Muslims. Plus, many accounts are in the name of MCA accounts. The main factor underlying the FUI Sul-Teng management, namely the individual factor concerned (perception) where the FUI Sul-Teng administrators themselves are the object of research responding to Muslim news on the MCA account, while the individual is supported by several factors, namely based on attitude, experience, knowledge, and hope. Regarding the news observed by Muslims. Then there is the target of perception. Each of the FUI Central Sulawesi administrators provides a perception based on various events contained in Muslim news, especially on the MCA account via Facebook. Then the situation, which was observed by the community administrators in viewing information about Muslims on the MCA account via Facebook.